Public Perception About Pandemic Risk - Widiyanti, Baiq Liana (Universitas Sebelas Maret, 2020)
This research motivated by the prevalence of the pandemic myth, namely that a pandemic is unavoidable and thus nothing to be worried about, and the health sector which should manage risks, and the risk of a pandemic, is not a development problem. This will lead to a poor understanding of pandemic risks, minimal preparedness and inadequate prevention. Examining the reasons this myth persists can help improve risk management associated with pandemics. Perceptions of risk play an important role in shaping health-related behaviors in controlling infectious diseases. The aim of this study is to assess risk perceptions and behavioral changes in response to a pandemic. This research is a qualitative research, with descriptive analysis techniques. The results showed that most people were apathetic in responding to pandemic conditions.